Grenseløst Agder Det som skilte og det som bandt - Eide Johnsen, Berit; Vadum, Kristoffer (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"Grenseløst Agder. Det som skilte og det som bandt highlights different aspects of the history of Norwegian region, Agder, as well as seeking to understand the regions present and future. The occation is the merging of the the two sub-regions Aust-Agder and Vest-Agder into Agder which took place January 1st of 2020. "